Three pillars of physical distancing: anxiety, prosociality, and rule compliance during the COVID-19 pandemic - Twardawski, Mathias; Steindorf, Lena; Thielmann, Isabel (Collabra: Psychology, 2021)
The outbreak of a global pandemic such as COVID-19 poses a challenge for societies across the world. Lacking both vaccination and medical treatment, the only way to combat the spread of a virus in its early stages are behavioral measures, particularly physical distancing behavior. The present work proposes three pillars of individuals’ engagement in physical distancing: anxiety, prosociality, and rule compliance. In a large (N = 1,504), pre-registered study among German adults, we studied both situation-specific tendencies and stable personality traits that are theoretically associated with these pillars in relation to self-reported physical distancing behavior and underlying motives. Results supported the importance of each of the proposed pillars for physical distancing behavior. That is, for each pillar, we found (some) relations of the corresponding tendencies and personality traits with physical distancing (motives) as expected. Overall, the project provides a comprehensive picture of physical distancing behavior during the COVID-19 pandemic.